1995
DOI: 10.1007/bf00286765
|View full text |Cite
|
Sign up to set email alerts
|

Significance of antibodies to cardiolipin in unselected patients with systemic lupus erythematosus: clinical and laboratory associations

Abstract: In a multicentre study anticardiolipin antibodies of the IgG and IgM isotypes were measured by a solid phase enzyme immunoassay in 368 patients with systemic lupus erythematosus (SLE) who were not selected on the basis of features of antiphospholipid syndrome. Clinical and laboratory associations of increased levels of anticardiolipin antibodies were evaluated. IgG and IgM antibodies to cardiolipin were documented in 224 (60.9%) and 128 (34.8%) patients, respectively. Regarding the symptoms of antiphospholipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…The data of this and other studies revealed that in addition to IgM anti-dsDNA antibodies, also IgM rheumatoid factors (manuscript in preparation), IgM anti-cardiolipin antibodies [9] and elevated serum IgM (data not shown) correlated negatively with nephritis. These parameters were not independent of each other: a pronounced positive association between IgM anti-dsDNA antibodies and elevated serum IgM or IgM anti-cardiolipin antibodies could be observed (Table 3).…”
Section: Association Of Igm Anti-dsdna Antibodies With Previous Drug mentioning
confidence: 68%
See 3 more Smart Citations
“…The data of this and other studies revealed that in addition to IgM anti-dsDNA antibodies, also IgM rheumatoid factors (manuscript in preparation), IgM anti-cardiolipin antibodies [9] and elevated serum IgM (data not shown) correlated negatively with nephritis. These parameters were not independent of each other: a pronounced positive association between IgM anti-dsDNA antibodies and elevated serum IgM or IgM anti-cardiolipin antibodies could be observed (Table 3).…”
Section: Association Of Igm Anti-dsdna Antibodies With Previous Drug mentioning
confidence: 68%
“…Sera 352 SLE sera were obtained from aliquots of a stock frozen at -70°C that was previously collected in the German SLE study [9,10,11,12,13]. All 352 patients fulfilled at least four of the ACR criteria for the diagnosis of SLE [3,4].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Antiphospholipid antibody (aPL) is another autoantibody that can occur in either the presence of or the absence of SLE, or even in healthy individuals. Antiphospholipid antibodies also occur in primary antiphospholipid syndrome (APS), viral infections (most notably human immunodeficiency virus), malignancy, and other autoimmune diseases (4)(5)(6).…”
mentioning
confidence: 99%